Cognitive emotion regulation in children as related to their parenting style, family type and gender - Karim, AKM Rezaul; Sharafat, Tania; Mahmud, Abu Yusuf (Journal of the Asiatic Society of Bangladesh, Science, 2014)
This study aimed to investigate whether cognitive emotion regulation in children varies with parenting style, family type and gender. Toward this end, cognitive emotion regulation and perceived parenting style of 206 school children were measured. Standard regression analyses of data revealed that the models were significant and explained 17.3% of the variance in adaptive emotion regulation (Adjusted R²=0.173; F=9.579, p<.001), and 7.1% of the variance in less adaptive emotion regulation (Adjusted R²=.071, F=4.135, p=.001). Results showed that childrens cognitive emotion regulation is functionally associated with parenting style, but not with family type and their gender. Amongst the three types of parenting, authoritative parenting was the strongest predictor of overall adaptive emotion regulation while authoritarian parenting was the strongest predictor of overall less adaptive emotion regulation. Permissive parenting has impact on neither adaptive nor less adaptive emotion regulation. The findings have implications for parents, caregivers, child psychologists and other professionals working with children/ adolescents. DOI: http://dx.doi.org/10.3329/jasbs.v39i2.17860 J. Asiat. Soc. Bangladesh, Sci. 39(2): 211-220, December 2013